2014
DOI: 10.1039/c4md00255e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-brominated phosphonates and their application as phosphate bioisosteres

Abstract: Substrate phosphorylation is a key modulator of signal transduction. Abnormal phosphorylation in vivo is implicated in many diseases including cancer, diabetes, and Alzheimer's disease. Inhibitors of phosphaterecognizing proteins have potential as medicinal agents as well as tools to study phosphorylation pathways. A well-known and common inhibition strategy is to synthetically replace the labile phosphate moiety with a non-hydrolyzable phosphonate. Fully saturated, a-fluoro and a,a-difluorophosphonates are of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 105 publications
(279 reference statements)
0
5
0
Order By: Relevance
“…However, replacement of the phenolic oxygen atom with a non-polar methylene group may decrease affinity for the active site and also reduce water solubility. 102 To address these issues, medicinal chemists replaced the hydrogens on the α-carbon with halogen atoms, to make the phosphonate an effective electronic isostere of the phosphate group. Chen et al synthesized phosphonodifluoromethyl phenylalanine (F 2 Pmp) as a nonhydrolyzable pTyr mimetic.…”
Section: Covalent Ptp Inhibitorsmentioning
confidence: 99%
“…However, replacement of the phenolic oxygen atom with a non-polar methylene group may decrease affinity for the active site and also reduce water solubility. 102 To address these issues, medicinal chemists replaced the hydrogens on the α-carbon with halogen atoms, to make the phosphonate an effective electronic isostere of the phosphate group. Chen et al synthesized phosphonodifluoromethyl phenylalanine (F 2 Pmp) as a nonhydrolyzable pTyr mimetic.…”
Section: Covalent Ptp Inhibitorsmentioning
confidence: 99%
“…12 Alternatively, on treatment of phosphonate 1a with ethane-1,2-dithiol (1.2 equiv) and PTSA (1 equiv) in refluxing chloroform, we have observed the formation of the desired thioketal 2a in 80% yield, together with the compound 2a' (15%) resulting from a further conjugate addition of ethane-1,2-dithiol on the enone moiety of the ketal 2a (Scheme 1). Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, all the reactions of compound 1a either with NBS (AIBN in CCl4) or under the previous conditions (NaH or LDA), with the considered halogenated derivatives failed. 12 Next, we explored the reaction of Wittig-Horner starting from the additon of the ketophosphonate 1a to a suspension of NaH (4 equiv) in THF at 0 °C then at room temperature, followed by the addition of benzaldehyde (2 equiv). We have observed that, at room temperature, no reaction occurred but in refluxing THF, an incomplete aromatization of 1a took place.…”
Section: Introductionmentioning
confidence: 99%
“…Organophosphorus compounds present an essential role in nature once their reactivity drives most biological processes [1–3] . Among the different class of organophosphorus compounds, phosphonates are explored in a variety of applications, such as in medicinal chemistry, [4–8] due to their physical‐chemical parameters similar to carboxylic acid analogs, and as phosphine ligands, because their modular properties [9–12] . Additionally, phosphonates have played a key position in the agrochemical field, [13–15] e. g. the herbicide glyphosate is one of the most widely used herbicides [16] …”
Section: Introductionmentioning
confidence: 99%